Comparison of stool antigen test with histological examination of gastric biopsy for detection of Helicobacter Pylori infection in children with nodular antritis. - Ibrahim, Ali; Dawod, Ali; Omran, Razan (Latakia University Journal -Medical Sciences Series, 2020)
OBJCTIVE:Helicobacterpylori (H.pylori) is a slow-growing gram-negative, microaerophilic bacterium that colonizes the gastric mucosa. H.pylori infection is acquired during the first decade of life and unless eradicated causes life-long infection. The tests applied for H. pylori diagnosis are grouped as either invasive(requiring endoscopy) or non-invasive methods.The aim of this study was to evaluate the accuracy of Helicobacter pylori stool antigen (HPSA) as a non-invasive test in comparison with histological examination of gastric biopsy as a reference test to detect the infection in children with nodular antritis. Methods and Patients :The study included 109 children with a median age of 10 years who reffered for endoscopy at Tishreen University Hospital ,Lattakia,Syria between 2018-2019, because of several indications. All of those children were have nodular antritis and we took biopsies from gastric antrum to detect H.pylori infection by histological examination . Faeces samples were analysed by HPSA test which uses immunochromatographic assay. Results: Of 71 children who were positive by histology ,53 were H.pylori stool antigen positive and of 38 patients with negative histology ,21 had negative stool test. Agreement coefficient (Kappa) was 0.29 . The sensitivity and specificity of the test were (74.6% and 55.2% respectively) compared with the gastric biopsy. The positive and negative predictive values were 75.7% and 53.8% respectively. Conclusion: The accuracy of HPSA is relatively low in developing countries. For this reason, the gastric biopsy is still the suggestive test for diagnosing in symptomatic children. HPSA test may be benefit in screening studies. هدف الدراسة: إن جرثومة الملوية البوّابيّة هي جرثومة سلبية الغرام ،بطيئة النمو ، مُحبّة للهواء بشكل خفيف، تستعمر المخاطية المعدية. يُكتسَب الإنتان عادةً خلال العقد الأول من الحياة ويسبب إصابة مزمنة في حال عدم العلاج. تُصنّف الاختبارات المُستخدَمة في تشخيص الإنتان إلى اختبارات غازية (تحتاج إجراء تنظير هضمي علوي ) وأخرى غير غازية. تهدف الدراسة إلى تقييم دقة اختبار المستضدّات البرازية (كاختبار غاز ) بالمقارنة مع الفحص النسيجي لخزعة المعدة لكشف الإنتان عند الأطفال المصابين بالتهاب الغار العقيدي. المواد والطرائق : شملت الدراسة 109 أطفال وسيط أعمارهم 10 سنوات ، تم تحويلهم لإجراء تنظير هضمي علوي لاستطبابات متعددة ، وذلك في مشفى تشرين الجامعي ، اللاذقية ، سوريا بين عامي 2018-2019. جميع هؤلاء الأطفال كانوا يعانون من التهاب الغار العقيدي ، وتم أخذ خزعات من غار المعدة للتحري عن وجود جرثومة الملويّة البوّابية نسيجياً. تم أخذ عينات براز أيضاً من جميع هؤلاء الأطفال ، لأجل التحري عن الجرثومة باستخدام اختبار المستضدات البرازية المستخدمة لتقنيّة الاستشراب المناعي. النتائج : جاءت نتائج الاختبار المستضدي في عينة البراز إيجابية لدى 53 طفلاً من بين 71 أثبت الفحص النسيجي إيجابيّتهم بالعدوى . كما جاءت نتائج الاختبار المستضدي سلبية لدى 21 طفلاً من بين 38 مريض أثبتت الخزعة سلبية الإنتان لديهم ، وبلغ معامل التوافق (كابا) 0.29 . كانت الحساسية والنوعية (74.6%, 55.2% على التوالي ) بالمقارنة مع الفحص النسيجي للخزعة . وكانت القيمة التنبؤية الإيجابية والسلبية ( 75.7%, 53.8 % على التوالي ) . الخلاصة : إن دقّة اختبار المستضدات البرازية لجرثومة الملويّة البوّابيّة متدنّية قليلاً ، لاسيّما في البلدان النامية. ولذلك فإن خزعة المعدة لاتزال هي الوسيلة التشخيصيّة المختارة لتشخيص الإنتان عند الأطفال العرضيّين . قد يفيد اختبار المستضدّات البرازيّة في الدراسات المسحيّة غالبا ً.